Effects of oestradiol treatment on hot flushes in men undergoing androgen deprivation therapy for prostate cancer: a randomised placebo-controlled trial. Issue 5 (29th September 2022) - Russell, Nicholas; Hoermann, Rudolf; Cheung, Ada S; Zajac, Jeffrey D; Grossmann, Mathis
Abstract: Objective: Most men undergoing androgen deprivation therapy (ADT) for prostate cancer experience hot flushes. Current treatments have low or limited evidence of efficacy. It is likely that oestradiol depletion is the mediator of these hot flushes, and transdermal oestradiol might be an effective treatment. Design: This is a 6-month randomised, placebo-controlled trial with the hypothesis that oestradiol would reduce hot flush frequency and intensity and improve quality of life (QoL). Methods: Seventy-eight participants receiving ADT were randomised to 0.9 mg of 0.1% oestradiol gel per day or matched placebo. Hot flush frequency and severity were assessed by 7-day diary at baseline, month 1, month 3, and month 6. QoL was assessed by validated questionnaire. Results: Oestradiol reduced daily hot flush frequency, with a mean adjusted difference (MAD) of −1.6 hot flushes per day (95% CI: −2.7 to −0.5; P = 0.04). The effect on weekly hot flush score was non-significant, with a MAD –19.6 (95% CI: −35.5 to −3.8; P = 0.11). On per protocol analysis, E2 significantly reduced daily hot flush frequency, with a MAD of −2.2 hot flushes per day (95% CI: −3.2 to −1.1; P = 0.001), and weekly hot flush score, with a MAD of −27.0 (−44.7 to −9.3; P = 0.02). Oestradiol had no significant effect on QoL. Conclusion: We confirmed our hypothesis of a clinical effect of assignment to oestradiol to reduce hot flush frequency in men with castrate testosterone due to ADT. Transdermal oestradiol could be considered for men with burdensome hot flushes in whom other treatments have failed as long as the risk of breast effects and fat gain are considered.